Assessing anthropogenic pollution in an oriented nature reserve using Anemonia viridis as a bioindicator - Teresa Bottari; Ilaria Guardamagna; Chiara Anastasia Bruno; Bilal Mghili; Francesca Fabrizi; Caterina Branca; Kannan Gunasekaran; Valeria Conti Nibali; Giovanna D'Angelo; Monique Mancuso (Marine Pollution Bulletin, 2026)

Anthropogenic particles accumulation in sea cucumbers: insights from a transitional environment - Monique Mancuso; Chiara Anastasia Bruno; Ilaria Guardamagna; Bilal Mghili; Francesca Fabrizi; Valeria Conti Nibali; Kannan Gunasekaran; Caterina Branca; Gian Marco Luna; Giovanna D'Angelo; Teresa Bottari (Marine Pollution Bulletin, 2026)

Antifungal activity and sensory analyses of chitosan aromatized with essential oils for the protection of fresh oranges and apples - Mario Riolo; Federico La Spada; Priscilla Farina; Soumia El Boumlasy; Roberta Ascrizzi; Francesca Venturi; Isabella Taglieri; Nunzio Tuccitto; Antonella Pane; Samuel Álvarez-García; Barbara Conti; Gianfranco Romanazzi; et al. (Postharvest Biology and Technology, 2026)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

In situ sonoporation to enhance the tumour uptake of silicon phthalocyanine and improve PDT effectiveness in a triple negative breast cancer murine model - Martina Capozza; Alberto Mangia; Michela Gagliardi; Rachele Stefania; Francesca Garello; Laura Conti; Enzo Terreno (Journal of Photochemistry and Photobiology B: Biology, 2025)

Growth performances of gilthead seabream (Sparus aurata) fed alternative diets for “circular” land-based IMTA production - Lorenzo Rossi; Carlo Bibbiani; Francesca Conti; Chiara Sangiacomo; Ilaria Marchioni; Elisa Merega; Simone Mancini; Alberto Pardossi; Baldassare Fronte (Aquaculture, 2025)

Phytochemical analysis on Stachys alpina L. different organs collected in Poland - Claudio Frezza; Francesca Conti; Adele Bosi; Luigi Scipione; Jan Oszmiański; Sabina Lachowicz-Wiśniewska; Daniela De Vita (Biochemical Systematics and Ecology, 2025)

Plastic pollution in brackish waters: Macroalgae as collectors of plastic debris - Francesca Fabrizi; Damiano Spagnuolo; Teresa Bottari; Bilal Mghili; Caterina Branca; Elisa Punzo; Mikołaj Mazurkiewicz; Valeria Conti Nibali; Giuseppa Genovese; Giovanna D’Angelo; Monique Mancuso (Journal of Hazardous Materials, 2025)

Plastic pollution in a special protected area for migratory birds - Caterina Branca; Francesca Fabrizi; Bilal Mghili; Valeria Conti-Nibali; Kannan Gunasekaran; Teresa Bottari; Monique Mancuso; Giovanna D’Angelo (Science of The Total Environment, 2025)

Belimumab 10 years later: how drug positioning has changed - Fulvia Ceccarelli; Francesco Natalucci; Claudia Ciancarella; Licia Picciariello; Valeria Moretti; Francesca Romana Spinelli; Cristiano Alessandri; Fabrizio Conti (Immunologic Research, 2024)
We analysed the change in the positioning of belimumab (BLM) in systemic lupus erythematosus (SLE) treatment in the first decade of real-life use, by providing data about patients treated by this biological drug in the Sapienza Lupus Cohort. We evaluated SLE patients treated by BLM according to the current clinical practice. Data of each patient were collected, focusing on previous and concomitant treatments. Finally, the drug retention rate was assessed. Since August 2013, 138 SLE patients started BLM (M/F 7/131; median age 49 years, IQR 13.25; median disease duration 214 months, IQR 180). To evaluate the change in BLM positioning, we divided patients according to the date of starting treatment as below: patients treated from 2013 to 2018 (period 1) and those treated since 2019 to date (period 2). Indeed, the median number of previous immunosuppressant drugs was significantly higher in patients treated in period 1 [3 (IQR 1.25) versus 1 (IQR 1.75), p = 0.0002]. Furthermore, 15.9% of patients treated in period 2 were not previously treated by immunosuppressant drugs, compared with 5.2% in period 1 ( p = 0.01). Finally, the 24-month drug survival was significantly higher in patients previously treated with ≤ 1 immunosuppressant drug in comparison with those treated with ≥ 2 drugs (69.1% versus 43.4%, p = 0.0097, HR 0.49; 95% CI 0.27–0.88). Our data clearly described the progressive anticipation of BLM prescription in the first 10 years of clinical practice, underlining as choosing earlier biological agents could positively influence the drug retention rate.

Chemo-enzymatic flow synthesis of nature-inspired phenolic carbonates and carbamates as antiradical and antimicrobial agents - Sara Vicinanza; Lara Mombelli; Francesca Annunziata; Silvia Donzella; Martina L. Contente; Chiara Borsari; Paola Conti; Gabriele Meroni; Francesco Molinari; Piera Anna Martino; Andrea Pinto; Lucia Tamborini (Sustainable Chemistry and Pharmacy, 2024)

Physicochemical and repellent properties of chitosan films loaded with essential oils for producing an active packaging effective against the food pest Sitophilus oryzae - Tasnim Djebbi; Roberta Ascrizzi; Stefano Bedini; Priscilla Farina; Chiara Sanmartin; Jouda Mediouni Ben Jemâa; Maria Francesca Bozzini; Guido Flamini; Barbara Conti (Journal of Stored Products Research, 2024)

Effect of light and feeding regimes on the daily rhythm of thermal preference in Nile tilapia (Oreochromis niloticus) - Gonzalo de Alba; Francesca Conti; Jorge Sánchez; Laura Michelle Godoy; Francisco Javier Sánchez-Vázquez; José Fernando López-Olmeda; Luisa María Vera (Aquaculture, 2024)

The protective combined effect of chitosan and essential oil coatings on cheese and cured meat against the oviposition of Piophila casei - Prangthip Parichanon; Roberta Ascrizzi; Camilla Tani; Chiara Sanmartin; Isabella Taglieri; Monica Macaluso; Guido Flamini; Ylenia Pieracci; Francesca Venturi; Barbara Conti (Food Bioscience, 2023)

Bioplastics on marine sandy shores: Effects on the key species Talitrus saltator (Montagu, 1808) - Tania Martellini; Alessandro Russo; Alessandra Cincinelli; Saul Santini; Cristiana Lofrumento; Matteo Baini; Samuele Ciattini; Luca Conti; Francesca Mostardini; Luca Mercatelli; Alberto Ugolini (Science of The Total Environment, 2023)

Validation and Verification of High-Fidelity Simulations of Thoracic Stent-Graft Implantation - Anna Ramella; Francesco Migliavacca; Jose Felix Rodriguez Matas; Frederic Heim; Francesca Dedola; Stefania Marconi; Michele Conti; Sara Allievi; Tim J. Mandigers; Daniele Bissacco; Maurizio Domanin; Santi Trimarchi; et al. (Annals of Biomedical Engineering, 2022)
Thoracic Endovascular Aortic Repair (TEVAR) is the preferred treatment option for thoracic aortic pathologies and consists of inserting a self-expandable stent-graft into the pathological region to restore the lumen. Computational models play a significant role in procedural planning and must be reliable. For this reason, in this work, high-fidelity Finite Element (FE) simulations are developed to model thoracic stent-grafts. Experimental crimp/release tests are performed to calibrate stent-grafts material parameters. Stent pre-stress is included in the stent-graft model. A new methodology for replicating device insertion and deployment with explicit FE simulations is proposed. To validate this simulation, the stent-graft is experimentally released into a 3D rigid aortic phantom with physiological anatomy and inspected in a computed tomography (CT) scan at different time points during deployment with an ad-hoc set-up. A verification analysis of the adopted modeling features compared to the literature is performed. With the proposed methodology the error with respect to the CT is on average 0.92 ± 0.64%, while it is higher when literature models are adopted (on average 4.77 ± 1.83%). The presented FE tool is versatile and customizable for different commercial devices and applicable to patient-specific analyses.

Deep Learning to Automatically Segment and Analyze Abdominal Aortic Aneurysm from Computed Tomography Angiography - Francesca Brutti; Alice Fantazzini; Alice Finotello; Lucas Omar Müller; Ferdinando Auricchio; Bianca Pane; Giovanni Spinella; Michele Conti (Cardiovascular Engineering and Technology, 2022)

Geological and hydrogeological reconstruction of the main aquifers of the Maltese islands - Alessio Barbagli; Enrico Guastaldi; Paolo Conti; Miriana Giannuzzi; Iacopo Borsi; Francesca Lotti; Paolo Basile; Lorenzo Favaro; Adrian Mallia; Rachel Xuereb; Michael Schembri; Julian Alexander Mamo; et al. (Hydrogeology Journal, 2021)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

First application of an Integrated Biological Response index to assess the ecotoxicological status of honeybees from rural and urban areas - Ilaria Caliani; Tommaso Campani; Barbara Conti; Francesca Cosci; Stefano Bedini; Antonella D’Agostino; Laura Giovanetti; Agata Di Noi; Silvia Casini (Environmental Science and Pollution Research, 2021)
Understanding the effects of environmental contaminants on honeybees is essential to minimize their impacts on these important pollinating insects. The aim of this study was to assess the ecotoxicological status of honeybees in environments undergoing different anthropic pressure: a wood (reference site), an orchard, an agricultural area, and an urban site, using a multi-biomarker approach. To synthetically represent the ecotoxicological status of the honeybees, the responses of the single biomarkers were integrated by the Integrated Biological Response (IBRv2) index. Overall, the strongest alteration of the ecotoxicological status (IBRv2 = 7.52) was detected in the bees from the orchard due to the alteration of metabolic and genotoxicity biomarkers indicating the presence of pesticides, metals, and lipophilic compounds. Honeybees from the cultivated area (IBRv2 = 7.18) revealed an alteration especially in neurotoxicity, metabolic, and genotoxicity biomarkers probably related to the presence of pesticides, especially fungicides. Finally, in the urban area (IBRv2 = 6.60), the biomarker results (GST, lysozyme, and hemocytes) indicated immunosuppression in the honeybees and the effects of the presence of lipophilic compounds and metals in the environment.

Circulating miRNAs expression as potential biomarkers of mild traumatic brain injury - Francesca Polito; Fausto Famà; Rosaria Oteri; Giovanni Raffa; Gianluca Vita; Alfredo Conti; Sacco Daniele; Vincenzo Macaione; Marcello Passalacqua; Salvatore Cardali; Rosa Maria Di Giorgio; Maria Gioffrè; et al. (Molecular Biology Reports, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Anti-mutated citrullinated vimentin antibodies in antiphospholipid syndrome: diagnostic value and relationship with clinical features - Cristiano Alessandri; Nancy Agmon-Levin; Fabrizio Conti; Carlo Perricone; Elena Ortona; Monica Pendolino; Antonella Capozzi; Federica Delunardo; Riccardo Mancini; Simona Truglia; Francesca Romana Spinelli; Fulvia Ceccarelli; et al. (Immunologic Research, 2017)

Properties and limits of some essential oils: chemical characterisation, antimicrobial activity, interaction with antibiotics and cytotoxicity - Francesca Scazzocchio; Stefania Garzoli; Cinzia Conti; Claudia Leone; Clio Renaioli; Federico Pepi; Letizia Angiolella (Natural Product Research, 2016)

Not just for beer: evaluation of spent hops (Humulus lupulus L.) as a source of eco-friendly repellents for insect pests of stored foods - Stefano Bedini; Guido Flamini; Jessica Girardi; Francesca Cosci; Barbara Conti (Journal of Pest Science, 2015)

Marine Microorganisms as Source of Stereoselective Esterases and Ketoreductases: Kinetic Resolution of a Prostaglandin Intermediate - Valerio De Vitis; Benedetta Guidi; Martina Letizia Contente; Tiziana Granato; Paola Conti; Francesco Molinari; Elena Crotti; Francesca Mapelli; Sara Borin; Daniele Daffonchio; Diego Romano (Marine Biotechnology, 2015)

Mycophenolate mofetil in systemic lupus erythematosus: results from a retrospective study in a large monocentric cohort and review of the literature - Fabrizio Conti; Fulvia Ceccarelli; Carlo Perricone; Laura Massaro; Enrica Cipriano; Viviana Antonella Pacucci; Simona Truglia; Francesca Miranda; Francesca Morello; Cristiano Alessandri; Francesca Romana Spinelli; Guido Valesini (Immunologic Research, 2014)

TRAF3IP2 gene and systemic lupus erythematosus: association with disease susceptibility and pericarditis development - Carlo Perricone; Cinzia Ciccacci; Fulvia Ceccarelli; Davide Di Fusco; Francesca Romana Spinelli; Enrica Cipriano; Giuseppe Novelli; Guido Valesini; Fabrizio Conti; Paola Borgiani (Immunogenetics, 2013)

Oviposition Behaviour of Lygus rugulipennis and its Preferences for Plant Wounds - Eric Conti; Francesca Frati; Gianandrea Salerno (Journal of Insect Behavior, 2012)

Influence of Feeding and Oviposition by Phytophagous Pentatomids on Photosynthesis of Herbaceous Plants - Violeta Velikova; Gianandrea Salerno; Francesca Frati; Ezio Peri; Eric Conti; Stefano Colazza; Francesco Loreto (Journal of Chemical Ecology, 2010)

Effects of the increase in neuronal fatty acids availability on food intake and satiety in mice - Roberto Coccurello; Antonio Caprioli; Sara Bellantuono; Francesca R. D’Amato; Roberto Conti; Fabio Giannessi; Franco Borsini; Anna Moles (Psychopharmacology, 2010)

Vicia faba-Lygus rugulipennis Interactions: Induced Plant Volatiles and Sex Pheromone Enhancement - Francesca Frati; Keith Chamberlain; Michael Birkett; Samuel Dufour; Patrick Mayon; Christine Woodcock; Lester Wadhams; John Pickett; Gianandrea Salerno; Eric Conti; Ferdinando Bin (Journal of Chemical Ecology, 2009)

Vicia faba–Lygus rugulipennis Interactions: Induced Plant Volatiles and Sex Pheromone Enhancement - Francesca Frati; Keith Chamberlain; Michael Birkett; Samuel Dufour; Patrick Mayon; Christine Woodcock; Lester Wadhams; John Pickett; Gianandrea Salerno; Eric Conti; Ferdinando Bin (Journal of Chemical Ecology, 2009)

Cytomorphological study on human submandibular gland following treatment with secretagogue drugs - Francesca Testa Riva; Roberto Puxeddu; Francesco Loy; Gabriele Conti; Alessandro Riva (Cell and Tissue Research, 2006)